Ultrastructural and molecular characterization of non-Helicobacter pylori species in the gastric mucosa of naturally infected pigs - Buck, Letícia Y.; Marutani, Victor; Lorenzetti, Elis; Alfieri, Amauri A.; Bracarense, Ana Paula L. (Brazilian Journal of Veterinary Pathology, 2018)
Infection by Helicobacter spp. has been associated with gastritis and ulcers in pigs and humans. Association between Helicobacter species and lesions can contribute to determine specific pathogenicity. The aim of this study was to describe ultrastructural aspects of Helicobacter spp. and identify Helicobacter species by PCR assay. Gastric samples from 13 naturally infected sows were analyzed. From these, 12 were positive for Helicobacter spp. 16S rRNA gene and seven were identified as H. suis. The species was not identified in five samples and all samples were negative for urease gene. The sequencing of rRNA gene of five samples showed similarity with H. suis and H. heilmannii type I. Seven samples positive for Helicobacter genus generated no sequenceable fragments. On ultrastructural study, three samples showed helical bacteria measuring 4 to 6 μm long, 0.5 to 0.8 μm width, 4 to 8 spirals and 2 to 6 bipolar flagella. Two samples showed bacteria measuring 9 to 10 μm in length, 0.5 μm width, 22 to 24 spirals and no flagella, characterizing Helicobacter non-H. pylori, but these samples were negative for H. suis. In conclusion, the results indicate that adult pigs are commonly infected by helical bacteria presenting different ultrastructural characteristics, suggesting that mixed infection is frequent.